Assessment of oral health in patients referred for an orthodontic examination to the Orthodontic Department of the Sarajevo Faculty of Dentistry - Redžepagić-Vražalica Lejla; Jelešković Azra; Mujić-Jahić Indira; Tiro Alisa; Džemidžić Vildana; Mušanović Alma (Balkan Stomatological Society, 2023)
Background/Aim: The objective of this research was to evaluate the level of oral hygiene, the prevalence of caries, and the condition of the soft tissues in children and adolescents referred for their first orthodontic examination. Material and Methods: The research was conducted at the Department of Orthodontics of Sarajevo University - at the Faculty of Dentistry with the Dental Clinical Center. A total of 300 patients with mixed and permanent dentition who were referred for their first orthodontic examination were included in the study. The patients were offered to sign a Letter of Informed Consent for this study. All patients were assigned a Decayed, Missing, and Filled Teeth (dmft/DMFT) index. Periodontal indices were evaluated on all first permanent molars and all permanent central incisors. The periodontal indices included the determination of PI,CI,GI, PBI. Results: The results were processed with the application of standard statistical methods, by using the SPSS computer program for statistical analyses (SPSS-Statistical Package for Social Sciences) Version 21.0. The results of this study show a high dmft and DMFT indices in patients referred for orthodontic examination. The dmft index value in the respondents with mixed dentition was 3.0 (1.0 - 6.0). The DMFT index value in the respondents with permanent dentition was 4.0 (0.0 - 6.0), while in the respondents with mixed dentition, it was 1.0 (0.0 - 3.0). Our research also shows that out of 300 patients referred to an orthodontist for their first orthodontic examination, 250 of them (83.33%) have demonstrated an increased value of the Plaque index. Conclusions: The results of this research should be peculiarly alarming for pedodontists and general dentists, cautioning them to implement caries prevention measures more intensively and make referrals to an orthodontist only in case of those patients who have been cured previously.